E-Rupee: India's Future through Central Bank Digital Currency - Opportunities & Hurdles (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Digital currencies, or cryptocurrencies, are gaining popularity. Some national central banks are contemplating digital currencies to address these issues and accelerate the cashless society transition. A Central Bank Digital Currency (CBDC) is a nation's official currency and central bank liabilities in digital form. Five companies appear to be working with the Reserve Bank of India (RBI) on the Central Bank Digital Currency pilot plan. You may recognise IDFC First Bank, HDFC Bank, State Bank of India, and ICICI Bank. Indian digital currency, the Digital Rupee, will be tested by the Reserve Bank of India on November 1, 2022.On October 31, 2022, the government agency in charge of the project stated that this pilot endeavour will facilitate secondary market transactions involving government securities. The RBI has chosen nine financial institutions to pilot the Digital Rupee. Bank of Baroda, State Bank of India, Union Bank of India, ICICI Bank, HDFC Bank, Kotak Mahindra Bank, IDFC First Bank, YES Bank, and HSBC are notable financial institutions. This study seeks to understand the growth of Central Bank Digital Currency (CBDC) in India, taking into account its global adoption to speed up transactions, improve security, and reduce physical currency production costs.